ISOLATED GUNSHOT URETERAL INJURY – CASE REPORT - Dejan Bratuš; Gregor Hlebič (Zdravniški Vestnik, 2004)
Background. In the article a case report of an eleven years old child who suffered an air rifle gunshot injury of his right ureter is presented. Methods. The child was admitted to the hospital without any subjective complaints while both ultrasound and CT scan showed a metallic alien body just below the hilus of his right kidney with no surrounding liquid collection. After the condition of the child had worsened with right lumbar and abdominal pain, the control CT scan showed a huge urinoma in his right retroperitoneum. Results. During a surgical exploration an ureteral injury was found with the pellet lying inside the right ureter just below the injury, causing an obstruction of the ureter. After the removal of the pellet and suturing of the ureter over a double J stent the child recovered without any sequels. Conclusions. The ureter is the least often injured genitourinary organ. The management of these injuries is usually straightforward and is primarily a problem of recognition at the initial presentation, especially of a patient with multiple injuries. The delayed presentation is principally responsible for the morbidity that is associated with a ureteral injury.